A framework for self-experimentation in personalized health. (7th December 2015) - Karkar, Ravi; Zia, Jasmine; Vilardaga, Roger; Mishra, Sonali R; Fogarty, James; Munson, Sean A; Kientz, Julie A
Abstract : Objective To describe an interdisciplinary and methodological framework for applying single case study designs to self-experimentation in personalized health. The authors examine the framework's applicability to various health conditions and present an initial case study with irritable bowel syndrome (IBS). Methods and Materials An in-depth literature review was performed to develop the framework and to identify absolute and desired health condition requirements for the application of this framework. The authors developed mobile application prototypes, storyboards, and process flows of the framework using IBS as the case study. The authors conducted three focus groups and an online survey using a human-centered design approach for assessing the framework's feasibility. Results All 6 focus group participants had a positive view about our framework and volunteered to participate in future studies. Most stated they would trust the results because it was their own data being analyzed. They were most concerned about confounds, nonmeaningful measures, and erroneous assumptions on the timing of trigger effects. Survey respondents ( N = 60) were more likely to be adherent to an 8- vs 12-day study length even if it meant lower confidence results. Discussion Implementation of the self-experimentation framework in a mobile application appears to be feasible for people with IBS. This framework can likely be applied to other health conditions. Considerations include the learning curve for teaching self-experimentation to non-experts and the challenges involved in operationalizing and customizing study designs. Conclusion Using mobile technology to guide people through self-experimentation to investigate health questions is a feasible and promising approach to advancing personalized health.